An investigation of the role of the amygdala in taste aversion learning - Arthur, James Brody (My University, 1974)
Contemporary theories of amygdaloid function postulate that the amygdala is involved in the association of events with aversive consequences or in the inhibition of responses. Experiment 1 investigated the possibility that the amygdala is necessary for the learning of a conditioned taste aversion, a task requiring the association of taste with gastric distress and subsequent response inhibition. The performance of a group of intact rats was compared with that of two groups of rats with basolateral or corticomedial amygdaloid lesions. Since the groups of rats with amygdaloid lesions were impaired in the task, it was suggested that the amygdala is involved in the successful acquisition of a conditioned taste aversion.
Keywords: Taste; Amygdaloid body